2017
DOI: 10.1108/mbr-03-2017-0016
|View full text |Cite
|
Sign up to set email alerts
|

Resource availability, international acquisition experience, and cross-border M&A target search

Abstract: Purpose The purpose of this study is to explain how factors relating to resource availability affect managerial risk-taking with regard to the geographic and institutional proximity of cross-border merger and acquisition (M&A) targets. The paper further considers the impact of organizational learning by testing the moderating effect of the acquiring firms’ prior international M&A experience. Design/methodology/approach This study uses linear regression with robust standard errors to account for depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 100 publications
(120 reference statements)
0
14
1
Order By: Relevance
“…Similarly, the results are in concurrence with Rahahleh and Wei (2012), Ahern (2008); Billett andQian (2008), Ismail (2008); Aktas et al (2007) and Doukas and Petmezas (2007), who have noted diminishing returns to frequent acquirers and in most studies, hubris hypothesis inter alia seems to be the dominant explanation for the observed return pattern. However, the results are in stark contrast with studies such as Galavotti et al (2017), Zakaria et al (2017); Rabbiosi et al (2012) and Haleblian and Finkelstein (1999), which indicate an improvement in the long-term performance of cross-border acquirers.…”
Section: Cross-border Acquisitionscontrasting
confidence: 99%
“…Similarly, the results are in concurrence with Rahahleh and Wei (2012), Ahern (2008); Billett andQian (2008), Ismail (2008); Aktas et al (2007) and Doukas and Petmezas (2007), who have noted diminishing returns to frequent acquirers and in most studies, hubris hypothesis inter alia seems to be the dominant explanation for the observed return pattern. However, the results are in stark contrast with studies such as Galavotti et al (2017), Zakaria et al (2017); Rabbiosi et al (2012) and Haleblian and Finkelstein (1999), which indicate an improvement in the long-term performance of cross-border acquirers.…”
Section: Cross-border Acquisitionscontrasting
confidence: 99%
“…For instance, we recognize the limitation of our control measure of international experience, perhaps, does not capture the multidimensional aspect of the construct (Sullivan, 1994). Prior international experience, particularly with respect to CBMAs (Galavotti et al , 2017; Zakaria et al , 2017), maybe an important variable worthy of additional consideration in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Two common streams of research on the risks of cross-border M&As have taken either a financial markets perspective or an organizational behavior perspective. Extant studies on the M&A risks take different theoretical underpinnings, and central hypotheses, such as financial, strategic and organizational, and process perspectives (Birkinshaw et al , 2000; Haspeslagh and Jemison, 1991; Zakaria et al , 2017).…”
Section: Literature Reviewmentioning
confidence: 99%